Practical pressure management for a gradual transition from intermittent to continuous water supply. Issue 3 (11th February 2022) - Sánchez, David H.; Sánchez-Navarro, Jesús R.; Navarro-Gómez, Carmen J.; Renteria, Marusia
Abstract: Cities in developing countries that do not consider water resources as the basis for sustainable growth usually accept intermittent water supply (IWS) as the alternative to satisfy the demand of the population. Networks designed as constant water supply (CWS) operated as IWS hinder a safe and reliable water supply; thus, feasible alternatives to return the operation to CWS are required. This paper presents a methodology based flow/pressure control to accomplish an efficient transformation from an IWS sector to a CWS in the City of Chihuahua, Mexico. The management of pressure at sector entrance and critical supply points leads to successful improvement of service, ensuring water availability with adequate pressure at the peak of demand, as well as reducing the supply of water volume by 58% compared to the sector operated in IWS. The methodology allowed the improvement of decision-making and operating policy for the water operating agency (WOA), fixing service deficiency, avoiding the loss of water volumes, and maintaining competent management control. Nonetheless, resistance to the transition of using automation and setting the volume/pressure consumption based on reliable data persists. The change process will be successful to the extent that the WOA efficiently channels the participation of the personnel. HIGHLIGHTS: Flow/pressure control using reliable data allowed an efficient transformation from IWS to CWS. Measurement/control equipment and real-time network monitoring were used to assess DMA behavior. Management at sector entrance and critical points lead to successful improvement of service. Water volume was reduced by 58% compared to the DMA operated in IWS. In 21 months the water savings estimation exceeds one full year of supply. Graphical Abstract